Iatrogenic choroidal neovascularization associated with subretinal gene therapy surgery - Kenneth W. Price; Mark E. Pennesi; Andreas K. Lauer; Steven T. Bailey (American Journal of Ophthalmology Case Reports, 2022)
Purpose: To report a case of iatrogenic choroidal neovascularization (CNV) developing one month after subretinal gene therapy surgery. Observations: A 16-year-old male with biallelic RPE65 mutation associated retinal dystrophy was treated with subretinal voretigene neparvovec in the left eye. During initiation of a balanced salt solution pre-bleb, a faint and transient subretinal hemorrhage was observed at the retinotomy site. One month post-operatively, multi-modal imaging detected a CNV and a break in Bruch's membrane at the retinotomy site. The asymptomatic CNV was observed without treatment and resolved spontaneously. Conclusions & importance: As subretinal gene therapy surgery becomes more common, clinicians should monitor for possible trauma induced CNV associated with retinotomy formation and subretinal injection.